2013
DOI: 10.3928/01477447-20130222-16
|View full text |Cite
|
Sign up to set email alerts
|

InterTan Nail Versus Proximal Femoral Nail Antirotation-Asia in the Treatment of Unstable Trochanteric Fractures

Abstract: The goal of this study was to compare the outcomes of unstable trochanteric fractures treated with the InterTan nail (Smith & Nephew, Memphis, Tennessee) and the Proximal Femoral Nail Antirotation (PFNA-II) (Synthes, Solothurn, Switzerland). A total of 132 consecutive patients with unstable trochanteric fractures of the femur were enrolled in the study. The only intervention was InterTan nail or PFNA-II fixation of the unstable trochanteric fractures. Follow-up occurred at 1, 3, 6, and 12 months postoperativel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
86
2
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(97 citation statements)
references
References 29 publications
5
86
2
4
Order By: Relevance
“…On average, each patient received 423.6 ml of blood or blood products. Repeated reduction and manipulation will increase operative and fluoroscopy time and intraoperative blood loss, especially in more unstable fracture types (18). In our study, the reduction was good in 67 (60.9 %), acceptable in 24 (21.4 %) and poor in 19 (17.2 %) cases.…”
Section: Discussionmentioning
confidence: 69%
“…On average, each patient received 423.6 ml of blood or blood products. Repeated reduction and manipulation will increase operative and fluoroscopy time and intraoperative blood loss, especially in more unstable fracture types (18). In our study, the reduction was good in 67 (60.9 %), acceptable in 24 (21.4 %) and poor in 19 (17.2 %) cases.…”
Section: Discussionmentioning
confidence: 69%
“…[20] In our study, the cut-out rate as a result of varus collapse was 4.5% in Group I, consistent with studies by Ruecker et al [21] Zhang et al have reported a cut-out rate of 1-3% in a PFNA group, whereas no patient has developed cut-out in the Intertan group. [19] In the biomechanical study of Huang et al, femoral strength, stability, and bearing capacity have been higher in the InterTAN group than in the PFNA group. [22] Lin has reported that the use of PFNs with two lag screws is effective to treat AO OTA A1-A2-A3 ITF.…”
Section: Discussionmentioning
confidence: 99%
“…The results have shown that the extent of shortening at the femoral neck is greater in the InterTAN than in the PFNA group, whereas all of the union rate, walking ability, Harris hip score, and hip range of motion, have been similar between the two groups. [19] Ulus …”
Section: Discussionmentioning
confidence: 99%
“…Biomechanical tests have shown that InterTan nail is superior to dynamic hip screws, demonstrating a longer survival under cycling loading and less head displacement. [21] In a clinical comparative study, Zhang et al [22] have reported that patients receiving InterTan experience less pain than those receiving PFNA asia system with postoperative complications occured in similar rates between groups. In InterTan group, we achieved slightly shorter operative and flouroscopy times than reported in this series while it took significanly longer than implanting PFNA or Talon distal fix nail/lag screw.…”
Section: Discussionmentioning
confidence: 99%